Estudo fitoquímico de Sidastrum micranthum (A. ST.-Hil.) Fryxell e Wissadula periplocifolia (L.) C. Presl: uma contribuição à quimiotaxonomia da família Malvaceae - Gomes, Roosevelt Albuquerque (2011)
A phytochemical study was accomplished with two members of Malvaceae family, Sidastrum micranthum (A. St.-Hil.) Fryxell and Wissadula periplocifolia (L.) C. Presl.. From the aerial parts of Sidastrum micranthum thirteen compounds were obtained using chromatographic methods: a sitosterol and stigmasterol mixture, phaeophytin a; 132- hydroxy-(132-S)-phaeophytin a, m-methoxy-p-hydroxy-benzaldeyde, sitosterol-3-O-A- D-glucopyranoside, orto-hydroxybenzoic acid, 3,5,7,3 ,4 -pentahydroxyflavonol, 5,7- di-hyidroxy-4 -methoxi-flavone, 5,4 -di-hydroxy-7-methoxy-flavone, 5,8-di-hydroxy- 7,4 -dimethoxyflavone, kaempferol-3-O-D-(6 -E-p-coumaroyl) glucopyranoside. From Wissadula periplocifolia (All plant) were isolated a sitosterol-3-O-Dglucopyranoside and stigmasterol-3-O-D-glucopyranosíde mixture, 5,7-di-hydroxy- 4 -methoxy-flavone, 5,8-di-hydroxy-7,4 -dimethoxy-flavone, luteolin 7-O-Dglucopyranoside. The structural identification of all compounds were made by means of spectroscopic methods such as Infrared Spectroscopy and 1H and 13C Nuclear Magnetic Resonance, with the add of two dimensional techniques, i.e. HOMOCOSY, HMQC, NOESY and HMBC.